Health utility value and its influencing factors among adult residents in Zhejiang province: a cross-sectional study using Shapley value decomposition analysis - Pinyuan DAI; Xiaoyan ZHOU; Hao WANG; Weiwei GONG; Jin PAN; Yunqi GUAN; Jieming ZHONG; Na LI (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the health utility value and its influencing factors among adult residents in Zhejiang province, and to provide a reference for health policy formulation and evaluation. MethodsA face-to-face survey using a self-developed questionnaire was conducted from September 2022 to February 2023 among 9 000 adult residents (≥ 18 years) recruited using a multistage random sampling technique from 30 districts/counties in Zhejiang province. Participants' health utility values were calculated and adjusted using the compound hierarchical ordered probit model (CHOPIT). Multiple linear regression model and Shapley value decomposition method were used to analyze the effects and contributions of influencing factors on participants' health utility values. ResultsThe mean health utility value was 0.703 ± 0.158 for 8 684 successfully surveyed participants. The Shapley value decomposition analysis showed that the Shapley value was 0.277 for demographic characteristics, 0.106 for socioeconomic status, 0.042 for accessibility of health services, 0.067 for behavioral habits, and 0.024 for health status, with attributable contributions of 53.67%, 20.62%, 8.16%, 12.95%, and 4.60% to the health utility value, respectively. The multiple linear stepwise regression model analysis showed that gender, age, education level, occupation, annual household income per capita, hypertension, and sleep quality were the main factors influencing the health utility value of the adult residents, with Shapley values/attributed contributions of 0.006/0.98%, 0.114/18.01%, 0.188/29.09%, 0.029/4.65%, 0.229/35.84%, 0.020/3.18%, and 0.052/8.25%, respectively, and being female, older age, lower education level, being retired, lower annual household income per capita, hypertension, and poor sleep quality were correlated with reduced health utility value of adult residents. ConclusionThe overall self-rated health of adult residents in Zhejiang province is relatively good. Attention should be paid to the health status of adult residents who are female, middle-aged and elderly, with low education and low household income, as well as those with hypertension and poor sleep quality, in order to further improve the health-related quality of life of residents.